Description of student organization motivation for Lembaga Dakwah Kampus Al-Ihsan UIN Antasari: Gambaran motivasi berorganisasi mahasiswa pengurus Lembaga Dakwah Kampus Al-Ihsan UIN Antasari - Romita Asrani; Akhmad Sagir; Shanty Komalasari (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
The purpose of this research is to know the description of students' organizational motivation and the factors that influence it. The subjects in the study were four students from the management of LDK Al-Ihsan UIN Antasari Banjarmasin. This research uses descriptive qualitative method. The method of data collection was done by interview technique. The results showed that the subject's organizational motivation was high and all factors influenced the organizational motivation of the student administrators of LDK Al-Ihsan UIN Antasari Banjarmasin.